Postavitev nog pri udarcih v odvisnosti od lokacije udarca pri vrhunskih igralcih skvoša - Rojnik, Sara (Šport (Ljubljana), 2021)
The squash technique is composed of individual interrelated and co-dependent technical elements in repeatable cycles. The initial phase of the cycle is the appropriate positioning of the player in the T-position, where the player - when the competitor strikes the ball - prepares him/herself to move towards the ball and finishes the phase by positioning at the time of hitting the ball. The results of the study were obtained from a sample of 19 matches in the British Grand Prix international tournament (Manchester, 2011). The sample consisted of 21 players who, at the time of the tournament, ranked from 1st to 65th in the official world ranking. The results were obtained using the Tracker system. In the front of the court, the players hit the ball in more than 95% of cases by positioning themselves in the lunge. This position was also more frequent when ball was struck in the middle court, whereas in the back court, their positioning was on both legs. A detailed analysis revealed that the players, on the backhand side, statistically significantly strike the ball in the correct lunge position, whereas on the forehand side, their positioning is incorrect. These differences can be a consequence of the different number of steps that players make while moving to a certain point or area of the court, as well as the differences in the forehand and backhand striking technique.
Keywords: gibanje; leg positioning when hitting a stroke; movement; postavitev nog pri udarcu; skvoš; sport; squash; strokes; šport; udarci